Validation and iteration of CT perfusion defined malignant profile thresholds for acute ischemic stroke. Issue 1 (January 2020) - Keenan, Kevin J; Christensen, Soren; Inoue, Manabu; Mlynash, Michael; Albers, Gregory W; Smith, Wade S
Background: Malignant profile computed tomography perfusion (CTP) lesions are associated with poor outcomes after administration of intravenous tissue-plasminogen activator (IV-tPA) for ischemic stroke. Aims: To determine whether published CTP-based lesion thresholds predictive of poor outcomes in a predominantly 8 cm of CTP anatomic coverage cohort would predict poor outcomes in an independent 4 cm of CTP anatomic coverage cohort and to generate optimized 4 cm CTP thresholds. Methods: Ischemic stroke patients with baseline CTP imaging with 4 cm of anatomic coverage before receiving IV-tPA at a single institution were retrospectively studied. Perfusion lesion time to maximum of tissue residue function (Tmax) and cerebral blood flow (CBF) volumes were determined using RAPID automated software. Fisher's exact tests assessed associations between lesion thresholds and outcomes. Receiver operating characteristic (ROC) curves generated optimized thresholds for 4 cm of CTP coverage. Results: Sixty-three patients were included. Poor outcomes were associated with published thresholds of Tmax >6 s > 103 mL, Tmax > 8 s > 86 mL, and Tmax > 10 s > 78 mL but not CBF core >53 mL. Thresholds optimized for 4 cm of CTP coverage and associated with poor outcomes were Tmax > 6 s > 100 mL, Tmax > 8 s > 65 mL, Tmax >10 s > 46 mL, and CBF core >39 mL. Conclusions: We validated the ability of published CTP Tmax lesion volume thresholds to predict poor outcomes despite IV-tPA in an independent cohort using only 4 cm of CTP anatomical coverage. A CBF > 39 mL threshold, rather than the predominantly 8 cm CTP coverage derived CBF threshold of >53 mL, was associated with poor outcomes in this 4 cm CTP coverage cohort.